Seamless phase II/III/IIIb clinical trial designs with different endpoints for different phases. Issue 22 (16th November 2020) - Quan, Hui; Luo, Xiaodong; Zhou, Tianyue; Zhao, Peng-Liang
Abstract: In a seamless phase II/III/IIIb trial, K ( K ≥ 2) doses versus placebo control are evaluated at phase II. Based on phase II results, one dose will be selected for phases III and IIIb. Pre-specified additional numbers of patients will be enrolled into the selected dose and placebo control during phases III and IIIb. Results of the phase III endpoint may be submitted for an early New Drug Application. Final analyses will be conducted for ultimate claims of treatment effects for the selected dose on the phase III and IIIb endpoints. Multiplicity adjustment is performed for the overall type I error rate control.